Eggs - Ritchie, Florence Rebecca (My University, 1904)
Introduction: In our study of biological subjects we have become familiar with cells of various shapes and sizes - both of animal and of vegetable organisms; but few, of us think of the egg of our common barnyard fowls as being merely a simple reproductive cell which may or may not have been fertilized. The egg cell of the hen with its simple nucleus remains a simple cell though its yellow yolk substance may increase to many times its original size. As soon as the egg is fertilized it assumes a different form. It then becomes the many celled yolk that we eat.
Citation: Ritchie, Florence Rebecca. Eggs. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Eggs; Cells; Cooking Eggs; Nutrition; Diet; Theses